Patient costs of diabetes mellitus care in public health care facilities in Kenya - Oyando, R; Njoroge, M; Nguhiu, P; Sigilai, A; Kirui, F; Mbui, J; Bukania, Z; Obala, A; Munge, K; Etyang, A; Barasa, E (Wiley, 2019)
OBJECTIVE: To estimate the direct and indirect costs of diabetes mellitus care at five public health facilities in Kenya.